A comprehensive dataset of morphological traits for Indian climbersZenodo - Abhishek Pujari; Nidhi Vastrad; Vivek Pandi; Vishnu Shreekara Bhat; Gayathri Rajendiran; Mahim Bhat; Vaishnavi Pai; Sruthi Raghavendra; Naveen Babu Kanda; Munisamy Anbarashan; Narayanaswamy Parthasarathy (Data in Brief, 2025)
Climbers are among the most conspicuous elements of tropical forest ecosystems, where they exhibit exceptional taxonomic diversity. Despite their ecological significance, climbers are notably underrepresented in global plant functional trait databases, limiting our understanding of their ecological strategies and adaptive responses to environmental variation. In India, climbers including both lianas and herbaceous vines constitute approximately 12 % of the country's total angiosperm flora. Here, we present a database comprising 41,056 unique data points covering 16 morphological traits related to the stem, leaf, flower, and fruit across 2566 climber species, representing approximately 98 % of the known climber species of India. This is the first comprehensive effort to systematically compile functional trait information for Indian climbers. The database captures both highly plastic traits, such as leaf shape, apex, and base (which vary across climatic gradients), and more conservative traits, such as fruit and flower types. Additionally, traits exhibiting ontogenetic variation, such as the presence or absence of leaf hairs at different developmental stages, are also documented. With the increasing integration of plant functional traits into ecological and evolutionary research, this dataset offers valuable opportunities to explore the adaptive strategies, ecological roles, and life-history patterns of climbers in tropical ecosystems.